The Influence of Social Media on the Electability of Political Parties in Cirebon in The 2024 Elections - Syaeful Anam; Jefik Zulfikar Hafidz; Am'mar Abdullah Arfan (Program Studi Hukum Tata Negara, 2025)
Elections are a stage for political parties and an embodiment of Indonesian Democracy as stated in article 1 paragraphs 2 and 3 of the 1945 Constitution. In the context of modern politics, social media has become a significant campaign tool for political parties to attract the attention of voters, influence public opinion, and expand the reach of political communication. Social Media impact on the Party's Popularity or Electability. This research aims to analyze the influence and impact of social media on the electability of political parties in the 2024 General Election (Pemilu), as well as the implementation of campaigns using social media from the perspective of Law no. 7 of 2017 concerning Elections, case study of political parties in Cirebon. The method used by researchers is a qualitative method using a Normative Juridical and Empirical Juridical Approach. Data collection techniques are observation, interviews and documentation. The conclusion of this research is that the effective use of social media has a positive correlation with increasing the electability of political parties, especially new parties that do not yet have high electability, on the other hand, parties that are old and have many cadres and have political figures who have been in parliament for a long time do not have much influence through social media on increasing the party's electability